Plagiarism: to what extent it is understood? - Wan Ali, Wan Zah; Ismail, Habsah; Tan, Tien Cheat (Elsevier, 2012)
Plagiarism has been identified as a problem since the 1600s. Nevertheless, this problem is becoming more alarming with the use of internet which provides the avenue for easy access for a student to plagiarise. This unethical act must be prevented to ensure that students’ behaviour and integrity are in line with moral virtues and values. Based on literature, one of the ways to overcome this problem is to examine students’ understanding of the concept of plagiarism. Hence, a study had been carried out amongst the university students aimed at identifying the extent of students’ understanding of the concept of plagiarism through the use of computer and information technology. This study used the survey method involving 327 students and data was collected through administration of a questionaire. This paper will thus discuss the findings of the study together with its implications in the effort to overcome the issue of plagiarism amongst students.